2.45 GHz rectenna with high gain for RF energy harvesting - Maizatul Alice Meor Said; Zahriladha Zakaria; Mohd Nor Husain; Mohamad Harris Misran; Faza Syahirah Mohd Noor (Universitas Ahmad Dahlan, 2019)
This paper presents a high gain rectenna at 2.45 GHz. Two layers low cost FR4 substrate has been used with air-gap technology for this fabricated rectenna. The proposed designs contain antenna and open stub rectifying circuits with feedline. With the dimension of 100 x 100 x 5 mm3, this rectenna can perform high gain. The technique of air gap approach has been used for this proposed rectenna design so as to increase the antenna gain. Second and third harmonics has been eliminated by the introducing of triangular slot and ground plane to the developed design. The proposed rectenna successfully achieved the output voltages reaches 0.46 V when the input power is 0 dBm respectively when the input power range is between -25 to 30 dBm. It is also can reach up to 6V when the maximum input power is applied. High gain, simple design, low profile and easy integration are the main advantages of this design of the rectenna when compared to past researchers.